2017
DOI: 10.1111/aor.13057
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Variability of Surface Motor Activation Zones in Hemiplegic Patients During Functional Electrical Stimulation Therapy Sessions

Abstract: The goal of this study was to investigate surface motor activation zones and their temporal variability using an advanced multi-pad functional electrical stimulation system. With this system motor responses are elicited through concurrent activation of electrode matrix pads collectively termed "virtual electrodes" (VEs) with appropriate stimulation parameters. We observed VEs used to produce selective wrist, finger, and thumb extension movements in 20 therapy sessions of 12 hemiplegic stroke patients. The VEs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…[10, 13]). In a recent study by Malešević et al [7], which analyzed the temporal and spatial variability of surface motor activation zones in electrode arrays in 20 FES sessions in stroke patients, it was reported that changes in the VE configuration for wrist, finger, and thumb extension were required each session for all patients. The authors concluded that an experimental (re-)calibration procedure is necessary for each therapy session.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[10, 13]). In a recent study by Malešević et al [7], which analyzed the temporal and spatial variability of surface motor activation zones in electrode arrays in 20 FES sessions in stroke patients, it was reported that changes in the VE configuration for wrist, finger, and thumb extension were required each session for all patients. The authors concluded that an experimental (re-)calibration procedure is necessary for each therapy session.…”
Section: Discussionmentioning
confidence: 99%
“…Electrode arrays consist of multiple, small elements, which can be activated separately. By activating multiple elements in a defined temporal pattern (synchronously/asynchronously), so-called virtual electrodes (VEs) can be formed [6, 7]. VEs can dynamically change their position, shape, and size.…”
Section: Introductionmentioning
confidence: 99%
“…Malešević et al of Tecnalia Serbia Ltd, Belgrade, Serbia to investigated surface motor activation zones and their temporal variability using an advanced multi‐pad functional electrical stimulation (FES) system. With this system motor responses are elicited through concurrent activation of electrode matrix pads collectively termed “virtual electrodes” (VEs) with appropriate stimulation parameters.…”
Section: Functional Electrical Stimulation and Musculoskeletal Supportmentioning
confidence: 99%
“…A drawback of electrotactile stimulation, amplified in multipad (array) systems, is the variability of elicited sensations. Even though sensitivity to electrotactile stimulation has some topological regularity [21], when observed on the level of precision needed for sensory substitution, significant intrasubject and temporal variability is observed [21, 22, 27, 28]. An additional concern is the significant overlap of preferred and uncomfortable amplitude ranges between different subjects as described in [21].…”
Section: Introductionmentioning
confidence: 99%